PERAN BPJS KESEHATAN PADA PENINGKATAN KESEJAHTERAAN EKONOMI MASYARAKAT DI MONTERADO STUDI TERHADAP IBU HAMIL - Deffrinica (JURNAL BORNEO AKCAYA, 2020)
The purpose of this study was to investigate the level of welfare of pregnant women before and after obtaining BPJS for Health Services. The research was a qualitative descriptive approach. It applied a focus group discussion (FGD) and structured interviews with a questionnaire. The samples were 24 pregnant women from the village of Goa Boma. The results showed that most pregnant women got the benefits of health services for giving birth and its recovering. Having this BPJS Health service, they could save the costs the medical examination and childbirth. These unpaid costs could be allocated for other household needs and / or to meet the needs of the baby who was just born. Even though they were treated in the second and third class, they calimed that the services were acceptable. class of health services they get is second and third class. Keywords: Health insurance, economic welfare, pregnant women, FGD